2019
DOI: 10.1091/mbc.e18-10-0609
|View full text |Cite
|
Sign up to set email alerts
|

Dissociation of membrane–chromatin contacts is required for proper chromosome segregation in mitosis

Abstract: The nuclear envelope (NE) aids in organizing the interphase genome by tethering chromatin to the nuclear periphery. During mitotic entry, NE–chromatin contacts are broken. Here, we report on the consequences of impaired NE removal from chromatin for cell division of human cells. Using a membrane–chromatin tether that cannot be dissociated when cells enter mitosis, we show that a failure in breaking membrane–chromatin interactions impairs mitotic chromatin organization, chromosome segregation and cytokinesis, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
43
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(47 citation statements)
references
References 60 publications
4
43
0
Order By: Relevance
“…Alternatively, or additionally, passive ER exclusion by spindle microtubules is thought to occur when mitotic phosphorylation of ERmicrotubule linking proteins disrupts their interaction with the spindle [7,12]. While the importance of ER membrane exclusion from the spindle is not clearly established, it has been proposed to facilitate movement of mitotic chromosomes [11,13], including metaphase chromosome congression and anaphase segregation of chromosomes [14] (Figure 1(b-c)).…”
Section: Introductionmentioning
confidence: 99%
“…Alternatively, or additionally, passive ER exclusion by spindle microtubules is thought to occur when mitotic phosphorylation of ERmicrotubule linking proteins disrupts their interaction with the spindle [7,12]. While the importance of ER membrane exclusion from the spindle is not clearly established, it has been proposed to facilitate movement of mitotic chromosomes [11,13], including metaphase chromosome congression and anaphase segregation of chromosomes [14] (Figure 1(b-c)).…”
Section: Introductionmentioning
confidence: 99%
“…In the course of prophase, the multifaceted interactions between INM proteins, chromatin and nuclear lamins are broken, allowing for the separation of membranes from chromatin and the partitioning of INM proteins into the mitotic ER network (Ellenberg et al, 1997, Yang et al, 1997. Exploiting a synthetic membrane-chromatin tethering system, we recently demonstrated that failed removal of membranes from chromatin impairs mitotic chromatin organization, chromosome segregation and cytokinesis, and perturbs post-mitotic nuclear morphology (Champion et al, 2019). Notably, also in yeasts with closed mitosis, the detachment of chromosomes from the NE is required for faithful chromosome segregation (Titos et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Also chromatin-associated interaction partners of INM proteins such as BAF are released from chromatin by mitotic phosphorylation (Samwer et al, 2017). After prophase, multiple mechanisms ensure that the ER does not re-associate with chromatin prematurely, before NE reformation starts in late anaphase (Champion et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The release of chromosomes from the NE, whether through breakdown of the NE or dissociation from an intact membrane, is a common feature of mitosis in eukaryotes 38–41 . Indeed, in cultured human cells, the artificial tethering of histones to ER membranes leads to chromatin bridges and failure in chromosome segregation and chromatin organisation 44 . Our data indicate that ESCRT-III/AAA-ATPase Vps4 functions to release heterochromatin from the INM and this active process is critical for normal progression through mitosis.…”
mentioning
confidence: 99%